2022
DOI: 10.3390/biomedicines10061298
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus Mitigates Osteoarthritis-Associated Pain, Cartilage Disintegration and Gut Microbiota Dysbiosis in an Experimental Murine OA Model

Abstract: To test probiotic therapy for osteoarthritis (OA), we administered Lactobacillus acidophilus (LA) by oral gavage (2×/week) after induction of OA by partial medial meniscectomy (PMM). Pain was assessed by von Frey filament and hot plate testing. Joint pathology and pain markers were comprehensively analyzed in knee joints, spinal cords, dorsal root ganglia and distal colon by Safranin O/fast green staining, immunofluorescence microscopy and RT-qPCR. LA acutely reduced inflammatory knee joint pain and prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In humans with OA, Streptococcus correlates with knee pain 15 ; serum LPS, a constituent of gram‐negative bacterial cell walls, is associated with obesity‐related knee OA, 16 and plasma microbial composition is associated with knee OA in patients with obesity 17 . Our group recently published a description of microbial DNA within human and murine cartilage and demonstrated changes associated with OA 9,18 . Comparing our current gut microbiome data with these cartilage data, we find concordance in some clades ( Lactobacillus and Ruminococcus associated with non‐OA or reduced‐OA state in both data sets) but discordance in others ( Clostridiales and Lachnospira associated with non‐OA cartilage but positively correlated with OA score in our current gut microbiome data), indicating a complex relationship between the gut and other body microbiome niches.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In humans with OA, Streptococcus correlates with knee pain 15 ; serum LPS, a constituent of gram‐negative bacterial cell walls, is associated with obesity‐related knee OA, 16 and plasma microbial composition is associated with knee OA in patients with obesity 17 . Our group recently published a description of microbial DNA within human and murine cartilage and demonstrated changes associated with OA 9,18 . Comparing our current gut microbiome data with these cartilage data, we find concordance in some clades ( Lactobacillus and Ruminococcus associated with non‐OA or reduced‐OA state in both data sets) but discordance in others ( Clostridiales and Lachnospira associated with non‐OA cartilage but positively correlated with OA score in our current gut microbiome data), indicating a complex relationship between the gut and other body microbiome niches.…”
Section: Discussionsupporting
confidence: 57%
“…17 Our group recently published a description of microbial DNA within human and murine cartilage and demonstrated changes associated with OA. 9,18 Comparing our current gut microbiome data with these cartilage data, we find concordance in some clades (Lactobacillus and Ruminococcus associated with non-OA or reduced-OA state in both data sets) but discordance in others (Clostridiales and Lachnospira associated with non-OA cartilage but positively correlated with OA score in our current gut microbiome data), indicating a complex relationship between the gut and other body microbiome niches. However, in agreement with several previous human and mouse OA and tissue regeneration studies, 8 we found gut Lactobacillus and related species to be strongly correlated with reduced pathology in the current study.…”
Section: Discussionmentioning
confidence: 54%
“…OA was induced in 12-week-old mice by partial medial meniscectomy (PMM) as described previously by our group 10 , 17 . Briefly, mice were pretreated with 0.1 mg / kg buprenorphine subcutaneously and then commonly anesthetized intraperitoneally with ketamine (100 mg/kg) and xylazine (5 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…The gut-joint axis has been studied in the context of various joint-related conditions, such as osteoarthritis and rheumatoid arthritis, where the composition of the gut microbiota has been shown to impact inflammation around the joint. 160 Treatment with certain probiotic bacteria has been shown to mitigate osteoarthritis-associated pain and cartilage degeneration in a mouse model 161 and improve clinical osteoarthritis index scores in patients. 162 Therefore, it is likely that the gut microbiota composition plays a role in the FBR to joint implants and other peripheral tissues.…”
Section: Gut Microbiotamentioning
confidence: 99%